Production of bioethanol from tropical woody biomass - Ahmed, Abu Saleh; Islam, Md. Saiful; Hoque, Md. Ashraful; Doraisingam, Yogeswaran (Scientific Online Publishing, 2014)
In this study, we used the hydrolysis fermentation method to convert woody biomass, corn stove, sawdust and oil palm empty fruit bunch (OPEFB) to bioethanol. The samples were first pretreated and hydrolyzed to obtain sugar. The sugar content were measured and recorded. Upon the addition of the yeast peptone dextrose (YPD) medium, the biomass solutions were fermented using conventional yeast and the ethanol obtained were measured and analyzed. The result shows that the OPEFB has the highest sugar content followed by the corn stove waste and finally the sawdust waste. The amount of ethanol obtained in the fermentation process was in line with the amount of mixed sugar content in the hydrolyzed solutions. The OPEFB exhibits the highest ethanol yield, followed by the corn stove waste, and finally the sawdust waste.